2014
DOI: 10.1183/09031936.00194213
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hospital admissions for pulmonary embolism in Spain from 2002 to 2011

Abstract: The aim of our study was to analyse changes in the incidence, diagnostic procedures, comorbidity, length of hospital stay, costs and in-hospital mortality of patients hospitalised for pulmonary embolism in Spain over a 10-year period.We included all patients who were hospitalised for pulmonary embolism (ICD-9-CM codes 415

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
54
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 36 publications
13
54
2
8
Order By: Relevance
“…In this study, the incidence of discharge of patients hospitalized with PE in Spain increased in patients with and without diabetes between 2004 and 2013. Our results are consistent with the increase in the incidence of PE reported during the last few decades . In addition, adjustment for possible confounders revealed that the incidence among diabetic men and women was 2.00 and 2.50 times higher than among non‐diabetic men and women.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the incidence of discharge of patients hospitalized with PE in Spain increased in patients with and without diabetes between 2004 and 2013. Our results are consistent with the increase in the incidence of PE reported during the last few decades . In addition, adjustment for possible confounders revealed that the incidence among diabetic men and women was 2.00 and 2.50 times higher than among non‐diabetic men and women.…”
Section: Discussionsupporting
confidence: 91%
“…Third, health service use and associated costs in our clinical setting may not be representative of other countries with different healthcare systems. However, our cost estimations are comparable with those reported in a recent Spanish study [4].…”
Section: Discussionsupporting
confidence: 76%
“…Analysis of inpatient hospital discharge minimal clinical summaries in Belgium shows that the total number per year of inpatients with a primary diagnosis of PE increased by 19% between 2000 and 2010 [6], the mean length of stay slightly decreased over the past decade, from 13 days in 2002 to 11 days in 2011, and the mean cost per patient borne by social security increased by 17% during the same period. These data are consistent with those reported in a recent study in Spain [4].…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations